Case Report: Orthotic Treatment of Cranial Asymmetry Arising from Large Wormian Bone. Issue 2 (June 2022) - Kanack, Melissa D.; Greaney, John; Ganske, Ingrid M.
Wormian bones are accessory bones found within fontanelles and sutures. They are thought to be an anatomic variant, though presence of several Wormian bones may be associated with pathological conditions such as osteogenesis imperfecta. Positional deformational plagiocephaly results from external forces on the infant skull leading to brachycephaly or asymmetric flattening. Severe cases are commonly treated with a cranial orthotic helmet that guides remodeling of the growing skull into a more symmetric shape. There is little reported about the association between Wormian bones and development of plagiocephaly. We present a case of a patient with occipital cranial asymmetry (cranial asymmetry index 10.4%) who underwent CT scan to rule out lambdoidal synostosis. This demonstrated patent sutures and a large right-sided Wormian bone. He was successfully treated with helmet therapy to address the contralateral deformational plagiocephaly. Wormian bones may be an under-recognized cause of asymmetrical cranial shape, potentially coexisting with deformational plagiocephaly. This case reports a role for orthotic therapy in these situations, as in isolated deformational plagiocephaly, to minimize asymmetry exacerbated by positioning on the contralateral side.